Constraints of Grammar Teaching and Learning: a Case Study at Junior High School - Rasyimah Rasyimah; Dewi Kumala Sari; Henny Irawati (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
ABSTRACT: This study would like to analyse constraint of grammar teaching and learning process in junior high school. The goal of this study was to examine the grammar teaching and learning process and determine the constraints to that process. The design applied in this research is qualitative approach and the type is a case study. The researcher used questionnaires, interviews, and observation to gather the data for this study. The English teacher who taught in second year students and some students became the respondents. The result of research finds the deductive approach was applied in which the rules applied and the exercises were practised. There were four constraints of grammar teaching learning i.e., lack of students’ motivation, lack of teachers’ role, teachers’ method, and lack of materials. It is suggested that the exact plan, approach, and technique that would be most effective for junior high school kids must be determined by teachers. Keywords: constraints, grammar teaching, grammar learning.